The Qualification of a Student of Religion - According To Vedanta - Major (Dr.) Bela Malik , Dr. Dilip Pipara, (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2013)
An eligible student or a Seeker of Truth or God is called an Adhikari or Jignasu. He is a student of science of spiritual Conciousness or Parmarth. However, to qualify as one, he needs to posses certain attributes. According to Vedanta philosophy, an Adhikari should have acquired Good Sanskaras’ that are a kind of Spirit Culture’ inherited by bnirth on account of his exposure to spiritual knowledge in his previous lives and have acquird purity of mind, after being absolved from all sins. In his present life. he should be performing all the necessary Karmas (actions) that are prescribed in the scriptures, like the daily rutine of worship or Sadhana. He must carry out the obligatory actions prescribed for different occasions; such as those performed on the birth of a child etc. He must also have given up those actions that are focused towards attaining pleasures of different sorts, both in the current lifetime and in the afterlife. Prohibited actions should necessarily be abandoned. In other words, one should be doing only obligatory duties without entertaining any desire for their fruits and consequent pleasures, and obligatory duties with out entertaining any desire for their fruits and consequent pleasures, and thereby attaining purity of mind and heart.